CRIMINAL LAW POLICY AGAINST MINORS WHO ARE BULLYING PERPETRATORS IN THE CENTRAL KALIMANTAN REGIONAL POLICE - Kezia Friscilla Angelina; Tahasak Sahay; Yurika Fahliany Dewi (RADJA PUBLIKA, 2025)
This study aims to understand how criminal law policies are applied to minors who become perpetrators of bullying in the jurisdiction of the Central Kalimantan Regional Police. Using an empirical legal approach, this study examines the application of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA), particularly in the context of restorative justice. The research was conducted through literature review, interviews with police officers, and a review of juvenile case decision documents. The results indicate that juveniles as perpetrators of bullying cannot be treated the same as adults, because psychologically and socially, children are still in the development process. Therefore, resolving cases through diversion or mediation is a more appropriate option to create a sense of justice for all parties. In many cases, the police act not only as law enforcers but also as facilitators in the mediation process between the juvenile perpetrator and the victim, involving parents, schools, and counselors from the Child Protection Agency (BAPAS). However, the restorative approach cannot be applied arbitrarily because there are formal and material requirements that must be met. In addition, challenges faced by the police include a lack of evidence, victims' reluctance to speak out, and delays in reporting. To address these challenges, synergy between schools, families, and the community is needed so that the resolution process doesn't stop at mediation but also results in sustainable behavioral changes in children. This study recommends strengthening training for police officers, providing prevention education in schools, and optimizing the role of families in developing children's character to prevent future bullying.